An arylthiazyne derivative is a potent inhibitor of lipid peroxidation and ferroptosis providing neuroprotection in vitro and in vivo - Meike Hedwig Keuters (Nature Portfolio, 2021)
Abstract Lipid peroxidation-initiated ferroptosis is an iron-dependent mechanism of programmed cell death taking place in neurological diseases. Here we show that a condensed benzo[b]thiazine derivative small molecule with an arylthiazine backbone (ADA-409-052) inhibits tert-Butyl hydroperoxide (TBHP)-induced lipid peroxidation (LP) and protects against ferroptotic cell death triggered by glutathione (GSH) depletion or glutathione peroxidase 4 (GPx4) inhibition in neuronal cell lines. In addition, ADA-409-052 suppresses pro-inflammatory activation of BV2 microglia and protects N2a neuronal cells from cell death induced by pro-inflammatory RAW 264.7 macrophages. Moreover, ADA-409-052 efficiently reduces infarct volume, edema and expression of pro-inflammatory genes in a mouse model of thromboembolic stroke. Targeting ferroptosis may be a promising therapeutic strategy in neurological diseases involving severe neuronal death and neuroinflammation.